Buffet suppression in long-span suspension bridges - Limebeer, D; Graham, J; Zhao, X (2011)
We study the aerodynamic control of long-span suspension bridges and seek to raise the critical flutter wind speeds, while simultaneously suppressing buffeting. The control system design study is based on a simple flexible bridge section model that interacts with a constant-velocity air stream. A streamlined bridge deck is assumed and non-steady thin aerofoil theory is used to describe the interactions between the bridge deck and the air stream. Classical turbulence models, first developed in the aircraft industry, are used to model the buffet forces acting on the deck. While a wide variety of control systems is possible, we focus on a compensation scheme that can be implemented using passive mechanical components such as springs, dampers and a rack and pinion mechanism. A single-loop control system is investigated that controls a trailing-edge flap by sensing movements of the bridge deck; several such mechanisms are contemplated. The first finding is that the critical wind speed for flutter can be greatly increased, with good robustness characteristics, through passive feedback control. It is also possible simultaneously to suppress flutter using the same passive mechanical controller by solving a passive mixed H2/H control problem. The effect of flexible controller mounting arrangements are considered briefly. © 2011 Elsevier Ltd. All rights reserved.